PELAKSANAAN PEMEKARAN KECAMATAN SENTAJO RAYA KABUPATEN KUANTAN SINGINGI MENURUT PERATURAN PEMERINTAH NOMOR 19 TAHUN 2008 TENTANG KECAMATAN (STUDI TERHADAP PASAL 4 HURUF C DAN D) - KMS Novyar Satriawan; Fauziah Rahmah (JURNAL HUKUM DAS SOLLEN, 2018)
Formation, division, deletion and incorporation of the area aims to improve people's welfare through improving services, improving order and security and increasing relations between the center and the regions which relies on Government Regulation Number 19 of 2008 concerning Sub-Districts. Sentajo Raya Subdistrict in the process of its formation was full of obstacles as well as the rejection of a number of Benai District community members. The fundamental problem in the formation of Sentajo Raya District is the existence of deviations from Article 4 letters c and d, where there is a rejection from the Benai District community due to the absence of consultation with the Benai District community regarding the formation and retrieval of several villages from the Benai sub-district. The rejection occurred since the discourse on the formation of the sub-district until the formation of Sentajo Raya Sub-District became widely discussed in the formation of this sub-district because it was not accepted for the components involved in the expansion of both the preparatory area and the parent area. Date 27 July 2012 Draft Regional Regulations on Three Subdistricts namely Kuantan Hilir Seberang Subdistrict, Sentajo Raya District and Pucuk Rantau Subdistrict are stipulated as Kuantan Singingi District Regulation Number 24 of 2012 concerning Formation of Kuantan Hilir Seberang District, Sentajo Raya District and Pucuk Rantau District. Through these regional regulations, Kuantan Singingi Regency officially increased by 3 (three) new sub-districts and Sentajo Raya District was one of the results of the expansion of 2 (two) main sub-districts namely Kuantan Tengah District and Benai District.